Recessions, Retirement, and Social Security - Coile, Courtney C; Levine, Phillip B (American Economic Review, 2011)
This paper examines how labor market fluctuations around the time of retirement affect the labor force status and Social Security receipt of individuals ages 55 to 69 and the income of retirees in their 70s, using data from the March Current Population Survey, Census, and American Community Surveys. We find that workers are more likely to leave the labor force, to collect Social Security earlier, and to have lower Social Security income when they face a recession near retirement. The impact is greatest for the less-educated, who are more susceptible to job loss and rely more heavily on Social Security.